(untitled) (Revista Gestão & Conexões, 2013)
DOI: http://dx.doi.org/10.13071/regec.2317-5087.2012.1.1.4833.5-7 Apresenta a edição de lançamento da Revista Gestão & Conexões (Management and Connections Journal), v1, n1, jul./dez. 2012.